Improving Asthma Management: Patient–Pharmacist Partnership Program in Enhancing Therapy Adherence - Tatiana Makhinova; Jamie C. Barner; Carolyn M. Brown; Kristin M. Richards; Karen L. Rascati; Arpita Nag (Pharmacy, 2022)
Community pharmacist interventions can assist in improving adherence in patients with asthma. The objective of the study was to assess the feasibility of patient-centered counseling using the developed asthma-specific tools to identify barriers to adherence and identify their preliminary effect on adherence barrier score and asthma control. Adult patients with persistent asthma were invited to participate in a 3-month pre–post intervention study involving community pharmacist-provided patient-centered counseling. Bivariate analyses were conducted to determine whether there were changes in outcomes from the pre to post period. Of 36 recruited patients, 17 completed both pre and post surveys. At baseline, patients had a mean ACT score of 15.1 ± 3.5, with 94% having uncontrolled asthma, and an average of 4.2 ± 2.5 reported barriers. The following barriers were most common: not having an Asthma Action Plan (52.9%), use of inhaler more or less often than prescribed (47.1%) and forgetfulness (41.2%). The ACT score increased by 2.7 ± 5.4, which was not statistically significant; however, it might be clinically significant. Two barrier scores improved as a result of the intervention. Preliminary evidence on the feasibility of identifying and addressing patient-specific barriers to adherence delivered by pharmacists showed that it has the potential to resolve barriers and improve asthma outcomes.